2022
DOI: 10.3390/ijerph19020924
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Experiences during COVID-19 among a National, Multi-Lingual, Community-Based Sample of Asian Americans and Pacific Islanders: COMPASS Findings

Abstract: Reports of escalated discrimination among Asian Americans and Pacific Islanders (AAPIs) due to COVID-19 are alarming, making this a public health priority. However, there are limited empirical studies on the scope and impact of COVID-19-related discrimination among AAPIs. Using the COVID-19 Effects on the Mental and Physical Health of AAPI Survey Study (COMPASS) data (N = 4971; survey period: October 2020–February 2021), which is a U.S.-wide multi-lingual survey, we examined the prevalence of, and factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…Social determinants of health and contextual models suggest that race and ethnicity, socioeconomic status, and social environment are important factors related to experiences of discrimination and racial bias [14,15]. Research on discrimination and Asian American individuals has shown that perceived discrimination varies by age, gender, and other demographic characteristics [7,16,17]…”
Section: Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Social determinants of health and contextual models suggest that race and ethnicity, socioeconomic status, and social environment are important factors related to experiences of discrimination and racial bias [14,15]. Research on discrimination and Asian American individuals has shown that perceived discrimination varies by age, gender, and other demographic characteristics [7,16,17]…”
Section: Objectivesmentioning
confidence: 99%
“…Few studies collected data on discrimination experiences or incidents broken down by Asian American and Native Hawaiian and Pacific Islander ethnic groups. A large survey (N=4971) of Asian American and Pacific Islander participants found that 60.7% experienced discrimination during the COVID-19 pandemic, and reports of these experiences were particularly high for Hmong (80%), ethnic Chinese (64.7%), Korean (64.2%), Filipino (61.3%), Japanese (57.7%), Vietnamese (55.7%), Asian Indian (41.5%), and Native Hawaiian and Pacific Islander (40.5%) participants [ 7 ]. In another survey of >2400 Asian American and Pacific Islander women during January and February of 2022, Native Hawaiian and Pacific Islander women reported the highest percentage (80%) of reporting racism or discrimination incidents or harassment, followed by similar levels reported by East Asian (72%), South Asian (73%), and Southeast Asian (75%) women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence against Asians has sharply increased and become more visible since the COVID-19 pandemic in 2020 [ 1 , 2 , 3 , 4 , 5 ], which makes research on discrimination and its impact on the psychological well-being of Asians in the USA timely and urgent. In response to this important public health problem, research on anti-Asian discrimination has increased in recent years, documenting a significant association between discrimination, especially unfair treatment, and psychological distress [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], consistent with research on African Americans and other minority groups [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although AA/NHPIs represent a very diverse set of communities with unique sociocultural and socioeconomic characteristics, they share a similar history and experience of discrimination and marginalization in the U.S. that has been exacerbated by the COVID-19 pandemic with the rise in hate crimes against their communities. 3 , 4 The historical mistrust toward the intentions of government and science shared by AA/NHPI communities has resurfaced during this global pandemic, in part, complicating COVID-19 mitigation efforts in these communities. 5…”
Section: Introductionmentioning
confidence: 99%